Phytochemical Screening of Gogauke Bio Oil as an Excellent Bio-Product for Natural Resource Management Solutions in Papua - Mingle A Pistanty; Sarima; Wahyu Purwanjani (Postgraduate, University of Mataram, 2025)
The Potential of Papua's Gogauke for Bio-Excellent Superior Products Papua possesses abundant biodiversity, and the Provincial Government is committed to green growth and sustainable natural resource management. Based on Special Autonomy, the rights of indigenous communities to protect the forests are also recognized. Local plants are often overlooked, despite having great potential. One such plant is Gogauke (Centella asiatica), traditionally used by Papuans as medicine. This plant is known to have various benefits, such as anti-inflammatory properties, wound healing, and pain relief. The objective of this research is to determine the potential of gogauke as a natural raw material for the superior product